Total Phenol Content of Avicennia marina Leaf and Its Relationship to the Environmental Quality - Hastuti, Endah Dwi; Izzati, Munifatul; Darmanti, Sri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Environmental dynamic in the coastal area is suggested to affect the metabolite concentration in mangrove plants. This research aimed to study the concentration of total phenol in A. marina leaf and to analyze the effect of environmental parameters on total phenol content dynamics. Environmental parameters studied in this research was temperature, pH, DO, and salinity, as well as N, P, and C sediment content. Data analysis was carried out through multiple regression of natural logarithm transformed data. Laboratory analysis resulted the value of total phenol content in A. marina leaf ranging from 0.88 – 1.62% with the average concentration of 1.28 ± 0.28%. Regression analysis resulted the significant effect of temperature, DO, and sediment content P and C expressed in the formula: ln(TP) = 31.229 – 7.224ln(T) – 0.067ln(DO) – 1.054ln(P) – 1.241ln(C). The research implicated that the increasing value of those factors was approaching the suitable condition for A. marina. Thus, instead of increasing the phenol concentration, the parameters negatively effect the secondary metabolite. The result showed that increasing temperature, DO, and content of P and C reduced the stress in A. marina and reduce total phenol content. This suggests that low temperature, DO, P and C concentration provides more potential of phenolic products from A. marina.